2000
DOI: 10.1029/2000gl008501
|View full text |Cite
|
Sign up to set email alerts
|

Detailed plate boundary structure off northeast Japan coast

Abstract: Abstract. In 1997, a seismic experiment using an airgun array and ocean bottom seismographs (OBSs) was performed in the forearc region of the northeast Japan (NEJ) arc. The objectives of this experiment were to clarify whole of the velocity structure around the forearc region of NEJ arc including a detailed plate boundary structure and the heterogeneous structure. In this paper, we estimated the heterogeneous velocity structure around the forearc region of northeast Japan by applying 2-D ray tracing and travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…The large value of d c may be consistent with the idea that plate boundary is a fairly matured fault composed by thick shear zone and d c is larger for the thicker shear zone width in direct shear experiments of gouge layer (Marone, 1998). Although existence of thick shear zone is not directly observed in subduction zone, low velocity layer is found on plate boundary in Japan trench area (Miura et al, 2003;Takahashi et al, 2000). So called subduction channel (Vannucchi et al, 2008) is also a candidate of substance for a large d c fault.…”
Section: Model Setup In Subduction Zonesupporting
confidence: 70%
“…The large value of d c may be consistent with the idea that plate boundary is a fairly matured fault composed by thick shear zone and d c is larger for the thicker shear zone width in direct shear experiments of gouge layer (Marone, 1998). Although existence of thick shear zone is not directly observed in subduction zone, low velocity layer is found on plate boundary in Japan trench area (Miura et al, 2003;Takahashi et al, 2000). So called subduction channel (Vannucchi et al, 2008) is also a candidate of substance for a large d c fault.…”
Section: Model Setup In Subduction Zonesupporting
confidence: 70%
“…As previously shown, it is quite likely that a thin low‐velocity zone is present along the plate boundary at depths between ∼12–16 km, resulting in the observed high‐amplitude P2P phases. A thin low‐velocity zone along the plate boundary at a depth of 10–30 km has been considered to indicate the presence of fluid along the plate boundary [e.g., Takahashi et al , 2000; Fujie et al , 2002; Kodaira et al , 2002]. Considering the interpretation that the increase in velocity within oceanic layer 2 is caused by cementation of internal fractures due to the subduction process (as mentioned above), it seems reasonable to consider that the thin low‐velocity zone is a result of trapped fluid dewatered from the oceanic layer below.…”
Section: Discussionmentioning
confidence: 99%
“…A weak seismic coupling could be due to the presence of unconsolidated or partly consolidated sediments between crusts of the arc side of the oceanic [e.g., Hartog and Schwartz , 1996]. At the Japan trench seismogenic zone area, it is known that the seismic coupling is <20% [e.g., Pacheco et al , 1993] and a low‐velocity zone exists between the subducting oceanic crust and the forearc crust of the northeastern Japan arc [e.g., Takahashi et al , 2000; Miura et al , 2000]. On the other hand, Ito et al [1999] showed that an average back‐slip rate of the western Nankai trough area is 4 cm/yr and that the seismic interplate coupling is strong.…”
Section: Crustal Model and Discussionmentioning
confidence: 99%